The Effect of Leg Muscle Strength Training on Side Kick Speed in FIKK UNM Pencak Silat Athletes - Hasan, Muh Said (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
This research is an experimental study that aims to determine the difference in the effect of leg muscle strength training on sickle kick speed in Pencak Silat FIKK UNM athletes. The population in this study was 20 athletes, random sampling was used, so the sample used was 20 athletes. The data analysis technique in this research is that the data from the test results in this research is quantitative data which will be analyzed descriptively using computerization. The results of the study are the results of the calculation of the normality test for the Leg Muscle Strength Training Group on Sickle Kick Speed Pencak Silat FIKK UNM Athletes. The results are based on the problem formulation which can be described as follows: 1). Leg muscle strength training has a significant effect on the speed of sickle kicks Pencak Silat FIKK UNM Athletes. 2). There is a significant difference in the effect of leg muscle strength training and no leg muscle strength training or the control group on sickle kick speed Pencak Silat FIKK UNM Athletes.